Successful staged operation for acute type A aortic dissection with paraplegia. (June 2013) - Ando, Takashi; Abe, Hiroyuki; Nagata, Tokuichiro; Makuuchi, Haruo
A 75-year-old man presented with both paraplegia and acute occlusion of the abdominal aorta at onset. Extraanatomical bypass was performed following spinal drainage. After 3 days, the ascending aorta replaced under cardiopulmonary bypass using the extraanatomical bypass graft for arterial cannulation. The abdominal aorta was replaced after 6 months. A staged operation is one of the options for acute aortic dissection with paraplegia and acute occlusion of the abdominal aorta.